2009
DOI: 10.1007/s10591-009-9084-8
|View full text |Cite
|
Sign up to set email alerts
|

Triggering Rage: Unresolved Trauma in Women’s Lives

Abstract: In this qualitative study we sought to explore the triggers involved in women's rage that are expressed towards their intimate partners. In-depth interviews were conducted with 37 incarcerated women who reported experiencing rage towards their partner. Unresolved trauma from childhood closely linked to current levels of adult rage; specific types of trauma that were reported included experiencing physical and sexual abuse, feeling unprotected by caretakers, and having observed domestic violence within their ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 56 publications
(58 reference statements)
0
15
0
1
Order By: Relevance
“…During in-depth interviews with women in medium-security prison, 90% of the participants reported that traumatic childhood memories triggered adult rage, and approximately 33% of the participants specifically described this traumatic event as CSA. Hypervigilance related to trauma might play a role, as these participants described perceived threat as a trigger to their adult violence (Flemke, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During in-depth interviews with women in medium-security prison, 90% of the participants reported that traumatic childhood memories triggered adult rage, and approximately 33% of the participants specifically described this traumatic event as CSA. Hypervigilance related to trauma might play a role, as these participants described perceived threat as a trigger to their adult violence (Flemke, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Women with a history of CSA exhibit significant amounts of aggressive behavior (Siegel, 2000) that tend to be directed toward their intimate partners, rather than other family members, acquaintances, or strangers (Graham & Wells, 2001). Qualitative research provides a context for this, and has explored the triggers of IPV perpetration among incarcerated women (Flemke, 2009). During in-depth interviews with women in medium-security prison, 90% of the participants reported that traumatic childhood memories triggered adult rage, and approximately 33% of the participants specifically described this traumatic event as CSA.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the theory and research reviewed here, difficulty in self-regulating emotions is a common lasting effect of childhood abuse (Cook et al, 2005) and a hallmark of complex trauma/ DESNOS . Focusing treatment on selfregulation (Courtois, 2004), such as detecting signals that one's body sends prior to rage detonation (Flemke, 2009), in effort to more effectively manage overwhelming emotions, would be key for helping women resist violent attacks. Luxenberg, Spinazzola, Hidalgo, et al's (2001) discussion of treating complex trauma illustrates one possible way in which a focus on self-soothing techniques can be incorporated into a treatment model.…”
Section: Treatment Implicationsmentioning
confidence: 99%
“…Emerging research shows an interconnected relationship between women's experiences of childhood abuse and their use of intimate partner violence (IPV) in adulthood (Feerick, Haugaard, & Hien, 2002;Flemke, 2009;Kernsmith, 2005;Sullivan, Meese, Swan, Mazure, & Snow, 2005;Swan, Gambone, Fields, Sullivan, & Snow, 2005;Swan & Snow, 2003;White & Widom, 2003;Widom, Schuck, & White, 2006). Years of research on both the dynamics of IPV and the long-term impacts of childhood abuse provide theoretical frameworks for understanding the link between the two as well as treatment options available.…”
mentioning
confidence: 99%
“…Despite socioeconomic status, religion, or race, the prevalence of IPV toward women in current marital/ partner relationships has been reported as high as 29% (Coker, Smith, & Fadden, 2005;Hathaway et al, 2000;Nelson, Baldwin, & Taylor, 2012;Nerøien & Schei, 2008;Svavarsdottir, 2010;Svavarsdottir & Orlygsdottir, 2009a). Furthermore, the relationship between IPV and health consequences has been well established in both clinical-and population-based studies (Flemke, 2009;Gharaibeh & Oweis, 2009;Krause, Kaltman, Goodman, & Dutton, 2007;Leiner, Compton, Houry, & Kaslow, 2008;Leppäkoski, Åstedt-Kurki, & Paavilainen, 2010;Svavarsdottir & Orlygsdottir, 2009a, 2009bWilson, Vidal, Wilson, & Salyer, 2012;Zlotnick, Capezza, & Parker, 2011).…”
mentioning
confidence: 99%